2017
DOI: 10.1007/s13205-017-0655-3
|View full text |Cite
|
Sign up to set email alerts
|

Pectin from muskmelon (Cucumis melo var. reticulatus) peels: extraction optimization and physicochemical properties

Abstract: Pectin derived from plant waste sources is currently focused as an economical and eco-friendly approach. Optimization of pectin extraction from muskmelon peel by response surface methodology (RSM) was investigated in this study. Box-Behnken Design (BBD) was used to identify the optimal level of the extraction variables such as time, pH and temperature. A second-order model equation for pectin extraction was obtained from multiple regression analysis of experimental data with the correlation coefficient (R 2 ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 34 publications
1
22
1
Order By: Relevance
“…Both FTIR spectra ( Figure 5) show similar bands to those of pectins found in the bibliography, especially the purified pectin with more intense peaks [19,20,31,70,72,73]. The peak at 3200-3500 cm −1 corresponds to OH stretching as a result of hydrogen bonding in pectin [19,31,71].…”
Section: Structural Characterizationsupporting
confidence: 61%
See 4 more Smart Citations
“…Both FTIR spectra ( Figure 5) show similar bands to those of pectins found in the bibliography, especially the purified pectin with more intense peaks [19,20,31,70,72,73]. The peak at 3200-3500 cm −1 corresponds to OH stretching as a result of hydrogen bonding in pectin [19,31,71].…”
Section: Structural Characterizationsupporting
confidence: 61%
“…As shown in Table 2 , the pectin yield was 16.59 g/100 g WIS, in dry weight, with a galacturonic acid content of 55.41% (91.23% of the galacturonic acid present in the original liquor). When comparing with the citric acid extraction, greatly differing melon peel pectin yields (3.24–29.48%) and lower galacturonic acid contents (indicating lower pectin purity) (47–48%) were reported [ 19 , 20 ]. Concerning similar raw materials, several autohydrolysis studies found a wide range in the galacturonic acid content of the obtained pectin, with higher values for the pomelo peels (76.62%) [ 54 ] and lower for apple pomace (48%) [ 55 ], both of which presented moderately higher pectin yields than this work (19.6 and 17.55%, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations